2019
DOI: 10.1007/s11661-019-05482-9
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Behavior of an AA4032 Piston Alloy with Cu and Er Additions upon High-Temperature Compressive Deformation

Abstract: Aluminum piston alloys of the AA4032 type are produced by direct-chill (DC) casting and subsequent forging; therefore, it is important to understand their thermomechanical behavior. In recent years, it was shown that additions of Cu and Er could improve mechanical properties of these alloys at room and high temperatures. In this work, we studied the constitutive behavior of AA4032-type alloys with and without Cu and Er additions. The experimental true stress-true strain curves were obtained by compression test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
2
3
0
Order By: Relevance
“…Phase composition presented in the Supplementary Table 1 is consistent with previous work on the 4032 alloy, 30 and also with the phase composition of multicomponent Al-Si piston alloys. 33 One should note that the Mg, Si, and Cu content in the fcc (Al) is consumed not only by Mg 2 Si phase but also by the eutectic (Si) and Fe-and Ni-bearing phases, which were observed in the BSD images presented in Figs.…”
Section: Extruded and Heat-treated Microstructuresupporting
confidence: 88%
See 2 more Smart Citations
“…Phase composition presented in the Supplementary Table 1 is consistent with previous work on the 4032 alloy, 30 and also with the phase composition of multicomponent Al-Si piston alloys. 33 One should note that the Mg, Si, and Cu content in the fcc (Al) is consumed not only by Mg 2 Si phase but also by the eutectic (Si) and Fe-and Ni-bearing phases, which were observed in the BSD images presented in Figs.…”
Section: Extruded and Heat-treated Microstructuresupporting
confidence: 88%
“…29 Similar findings were observed in Ref. 30 focused on DC casting and the compressive deformation of the AA4032 alloy with Er addition. On the other hand, EDX line-scan analysis conducted on the homogenized sample (Fig.…”
Section: As-cast and Homogenized Microstructuresupporting
confidence: 83%
See 1 more Smart Citation
“…Most of the publications have been devoted to investigating alloys with a small number of eutectic origin particles. However, it is known that such particles may significantly influence hot deformation behavior [29][30][31][32][33]. For example, it was found that the flow stress was lowered by decreasing the Al 3 Ni size at a low 0.03 volume fraction in binary Al-Ni alloys and intensive softening at large strains was achieved in the alloy with a 0.1 volume fraction of fine Al 3 Ni particles [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, few works have been devoted to investigating the effect of the Y and Er content phases on the hot deformation behavior of Al-Cu alloys. Chankitmunkong et al showed that the AA4032 alloy with 3.5Cu and 0.4Er had a lower activation energy of deformation compared to the base alloy without Er [33]. The alloy with Er demonstrated more polygonized grains at a low strain rate than the alloys without Er, indicating that Er hindered recrystallization development [33].…”
Section: Introductionmentioning
confidence: 99%